2009
DOI: 10.1002/pc.20802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dispersion on graphite nanosheet composites

Abstract: By intercalating and exfoliating natural graphite flakes, expanded graphite was obtained and used as the additive for making composites. The expanded graphite was composed of partly connected graphite nanosheets. Three types of composites were made, representing three levels of dispersing the graphite nanosheets. The first was the impregnation of epoxy resin to the expanded graphite by resin transfer molding. No dispersion was applied, and the expanded graphite can retain its original shape. The second was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Graphite doped composites and alloys have been created that utilize the superior thermal and mechanical properties of graphite to produce bulk materials with enhanced characteristics . However, poor dispersability and oxidation at temperatures above 600°C limit graphite's utilization as a high‐temperature ceramic additive . It is desirable to improve particle dispersion and wettability in suspensions and mixtures, to achieve more homogeneous properties in bulk materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Graphite doped composites and alloys have been created that utilize the superior thermal and mechanical properties of graphite to produce bulk materials with enhanced characteristics . However, poor dispersability and oxidation at temperatures above 600°C limit graphite's utilization as a high‐temperature ceramic additive . It is desirable to improve particle dispersion and wettability in suspensions and mixtures, to achieve more homogeneous properties in bulk materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, poor dispersability and oxidation at temperatures above 600°C limit graphite's utilization as a high-temperature ceramic additive. 5,6 It is desirable to improve particle dispersion and wettability in suspensions and mixtures, to achieve more homogeneous properties in bulk materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a dense CNT packing, resin becomes difficult to flow, and small voids in nanoscales can be formed. Because of the direct resin infiltration, the CNT contents of the present materials can be much higher, typically between 10 and 12 wt%, much higher than the value in typical bulk CNT composites .…”
Section: Resultsmentioning
confidence: 99%
“…Beyond a certain CNT fraction, the mixture will become too sticky to be processed by typical dispersion facilities, such as high‐speed mixers, sonication, and three‐roller mills . The previous works indicated that when the CNT loading reached 5 wt%, the mixture became a visco‐elastic material, and dispersion of CNTs becomes difficult for the three‐roller mill . Without proper dispersion, many CNTs are unable to be wetted and bonded by the resin, and the resulting mechanical behavior can be deteriorated.…”
Section: Introductionmentioning
confidence: 99%